Do MPV and NLR Values Differentiate Cholesteatoma from Chronic Otitis Media? - Mehmet Aslan; Mehmet Turan Çiçek (Van Tıp Dergisi, 2021)
INTRODUCTION: Chronic active otitis media(without cholesteatoma)and cholesteatoma are common ear pathologies that progress with a chronic inflammatory process, often causing damage, functional and anatomical loss. Differential diagnosis; provides foresight in determining the treatment to be applied and in terms of possible losses. Our study investigated the use of platelet indices, Neutrophil/Lymphocyte ratios, and Platelet/Lymphocyte ratios as auxiliary components in the differential diagnosis. METHODS: A total of 457 subjects were included in the study and the subjects were divided into three groups.The first group is the Cholesteatoma group consisting of 197 people(n =197),the second group is the Chronic Otitis Media Without Cholestatoma group,consisting of 140(n2=140) people,and the third group is the control group, consisting of 120(n3=120) people.The data of the subjects were evaluated statistically. RESULTS: In our study; The mean platelet volume in the cholesteatoma group(n1) was statistically significant compared to the other groups(p<0,033**). Neutrophil/lymphocyte ratios in the cholesteatoma group(n1) were statistically significant compared to the other groups(p<0,0024**). DISCUSSION AND CONCLUSION: In our study, we found that MPV and NLR values were significant in differentiating cases with cholesteatoma from chronic active otitis media. However, when compared with the literature, we found that NLR rates were more stable and determinative in cases with cholesteatoma.